Chronic urticaria: frequency of anti-HCV antibodies - Ahmed, Ijaz; Wahid, Zarnaz; Ahmed, Zaffar (Journal of Pakistan Association of Dermatologists, 2017)
Background Urticaria is defined as a skin disorder, clinically characterized by the presence of transient erythematous itchy weals presenting as an acute or a chronic disease, which may be caused by a wide variety of factors. Among infectious causes, hepatitis B virus is a known cause of urticaria; it would not be surprising if hepatitis C virus turns out to be an important one as well. The current study was aimed to determine the frequency of anti-BCV antibodies and HCV RNA in patients with chronic urticaria and to study HCV as a cause of urticaria. Â Patients and methods Of all the clinically diagnosed cases of chronic urticaria presenting in the outpatient department of Baqai Institute of Skin Diseases, patients fulfilling the inclusion criteria were enrolled in the study from 1st January, 2002 till 30th June, 2003 over a period of eighteen months. Patients belonging to either sex were aged 11 to 55 years. A written consent was taken from all the enrolled patients to carry out various blood tests. Sera of all the enrolled patients were tested for anti-HCV antibodies. Patients with positive enzyme-linked immunosorbent assay were also tested for viral RNA in their blood (polymerase chain reaction). Other relevant investigations were also carried out in seropositive patients i.e. liver function tests and ultrasound abdomen. Â Results Of the 114 patients enrolled in the study, 51 (44.8%) were males and 63 (55.2%) females, the gender ratio being 0.8. The maximum age of presentation was 55 years while minimum was 11 years. Maximum number of patients was 21-30 years of age (42.1%). Fifteen patients (13.2%) were positive for anti-HCV antibodies, comprising 9 females (7.8%) and 6 (5.6%) males (p<0.003). Maximum number of these patients (7.1%) was aged 21-30 years. Five (4.4%) of these seropositive subjects were also positive for HCV RNA including three males (2.6%) and two (1.8%) females. Deranged liver function tests were a feature in only 2 of these patients. Â Conclusion There may be a significant association of chronic urticaria with anti-HCV antibodies. Further studies are necessary to establish or refute an aetiopathogenetic role of HCV in this condition. Â